Clinical importance and prevalence of testicular microlithiasis in pediatric patients - Dutra,Robson Azevedo (2011)
PURPOSE: To evaluate the prevalence of testicular microlithiasis among pediatric patients with inguinoscrotal affections. METHODS: Between January 2005 and January 2010, we evaluated, prospectively 1504 children ranging from 1 to 15 years with inguinoscrotal affections with a high-frequency ultrasound system, which employs a 10-MHz transducer. RESULTS: Testicular microlithiasis was identified in 20 testes of eleven children (0.71% of 1504 patients evaluated), through an ultrasound scan. Testicular microlithiasis was found in 5 children with cryptorchidism (3.93% of 127 patients), 4 children with retractile testes (14.8% of 27 patients), 1 child with a hypotrophic testis (100% of 1 patient), and 1 child with inguinal hernia (0.07% of 1349 patients). The children with testicular microlithiasis were submitted to annual physical examinations and ultrasound evaluations. CONCLUSIONS: Testicular microlithiasis was a rare condition and occurred in 0.7% of the subjects studied. The association with cryptorchidism, retractile and hypotrophic testis was significant.